Harnessing Yoga and Naturopathic Nutrition for Constipation Management: An Observational Study (International Journal of Ayurveda and Pharma Research, 2025)
Chronic constipation is a prevalent gastrointestinal disorder associated with infrequent or difficult bowel movements and reduced quality of life. Pharmacological options often provide limited long-term relief and carry adverse effects. This study evaluated an integrative approach combining naturopathic dietary modifications and yoga-based practices. Materials and Methods: Thirty adults with clinically diagnosed chronic constipation underwent a 90-day intervention comprising fibre-rich dietary counselling and structured yoga practices aimed at improving gastrointestinal motility and abdominal function. Outcomes were assessed using the Patient Assessment of Constipation Symptoms (PAC-SYM), Constipation-Related Quality of Life Questionnaire (CRQOL), and Modified Bristol Stool Scale (MBSS). Statistical analyses included paired t-tests and repeated measures ANOVA. Results: Marked improvements were observed across all domains. PAC-SYM scores declined by 42.5% (10.62±1.80 to 6.10±1.17; p